Pravica do zdravljenja redkih bolezni v Sloveniji - Mišič, Luka (Delavci in delodajalci, 2026)
At the beginning of this year, the Parliament adopted the Act on the Fund for the Financing of the Treatment of Rare Diseases (ZSFZRB), intended to establish a systemic, earmarked source of funding for the treatment of rare diseases, which generally affect children. This makes the debate on the right to treatment of rare diseases - often linked to economic inaccessibility or the (non)existence of effective medication - particularly sensitive, as children represent a vulnerable group of the population. Additionally, a life not yet lived or not yet fulfilled is often considered more valuable than one already lived or fulfilled on an intuitive level. The paper, based on the constitutional right to healthcare and the foundations of compulsory health insurance, addresses the general regulation of the treatment of rare diseases in Slovenia, including the right to treatment abroad and the right or access to medicines, as well as the specific features introduced into the Slovenian legal system by the ZSFZRB.
Keywords: compulsory health insurance; medication; obvezno zdravstveno zavarovanje; pravica do zdravljenja; pravica do zdravljenja v tujini; pravica do zdravstvenega varstva; rare disease; redke bolezni; right to healthcare; right to healthcare abroad; zdravila